The Strategy of Madrasah Aliyah in Determining Minimum Values in Mathematics Subjects for Students Expected - Khairunnisa, Nadya; Septiany, Rafika; Bahri, Sudarul; Ayub, Muhamad (Universitas Ma'arif Lampung, 2024)
This research aims to find the range of minimum mathematics scores for a madrasah aliyah in Serang City. The research population was 888 students, and the sample size was 151 people, with the characteristics of the respondents being 46 men and 105 women. This sample was taken using a convenience sampling technique, namely madrasah aliyah students who had mastery of mathematics material and grades. The research data were analyzed using conjoint analysis and the Wastendorp price sensitivity test. Based on the optimal price point, a value of 76 is a mathematical value that is neither too low nor too high to achieve. Based on the acceptable price range, the minimum value range students consider to have mathematical ability is 73 to 80. Based on the indifference price, a value of 78 is considered ideal because this is a value that is considered neither low nor high to be achieved. The mathematics scores displayed by students can know, understand, and analyze mathematical problems in everyday life in the fair or even good category. Students are also expected to be polite, caring, confident, honest, disciplined, and responsible. When interacting with the community, students can demonstrate religious attitudes such as gratitude, praying before engaging in activities, and showing tolerance toward others who practice various religions in the moderate to good range.